COMPARATIVE PERFORMANCE OF TELLICHERRY GOATS UNDER EARLY WEANING AND CONVENTIONAL WEANING SYSTEM - S. Meenakshi Sundaram; T. Muthuramalingam; P. Tensingh Gnanaraj; T. Sivakumar; S.Vairamuthu; S. Rangasamy; E. Rachel Jemimah (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present work was formulated to evaluate the reproductive performance of Tellicherry does and the productive performance of their kids under the early weaning system. Second parity Tellicherry does aged between 2 – 2 1/2 years were divided into two groups namely treatment 1 (weaning at 90 days) and treatment 2 (weaning at 60 days) comprising of 20 does each. Reproductive parameters such as days to first estrum post kidding, days to conception post kidding, number of services per conception, and kidding interval of does were also recorded. Productive parameters such as body weight at birth, weaning, 6 months and 9 months of age, pre-weaning, post-weaning, and overall average daily gain, total biomass produced per kidding, and economics of rearing kids were recorded. Statistical analysis revealed no significant difference between weaning at 90 days and weaning at 60 days in terms of days to first estrum post kidding, days to conception post kidding, number of services per conception, and kidding interval. Kids born under the early weaning system and the conventional system had similar birth weights. Kids weaned early by 60 days had significantly lower (P < 0.01) weaning weight, body weight at six months, body weight at nine months, total biomass produced / kidding, pre-weaning average daily gain, post-weaning average daily gain, and overall average daily gain compared to kids weaned at 90 days. Early weaning did not improve the reproductive performance of Tellicherry does and had a negative impact on the productive performance of kids.